(untitled) (Journal of Family Sciences, 2023)
Abstract The family has an important role in preventing and reducing stunting cases. Family is the smallest unit in society. Family has a real influence on children’s health and nutrition. Efforts to be a family role have an effectively positive impact on high rates of stunting. Family has responsibilities to provide healthy food and nutritious food to children, and families have to create a healthy environment and provide good stimulation for children’s growth. In addition, the role of the family also involves education and understanding of good nutrition, disease prevention, and maintaining proper hygiene and sanitation for children. Families also have an essential role in accessing and using public health services, like visiting a midwife, nurse, or doctor, doing immunizations for children, and monitoring children’s growth at health facilities. This study confirms that the influence of social, economic, and health variables has a significant influence on the high incidence of stunting in Bekasi Regency. Several variables such as the Growth Risk of stunting families, prospective PUS, and catin (calon pengantin) access to health services are the causes of the high incidence of stunting in children in Bekasi Regency.